2011
DOI: 10.1177/1403494811401480
|View full text |Cite
|
Sign up to set email alerts
|

Work environment as predictor of long-term sickness absence: Linkage of self-reported DWECS data with the DREAM register

Abstract: Introduction: The present overview discusses ten papers dealing with four research topics using self-reported work environment in the Danish Work Environment Cohort Study (DWECS) linked with register data on long-term sickness absence (LTSA) in the Danish Register for Evaluation of Marginalisation (DREAM). Research topics: Research relied on selfreported data among 3000-5000 employees linked with registered LTSA data. Analyses were performed with Cox regression models. Risk groups: Kindergarten teachers and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 24 publications
3
56
0
4
Order By: Relevance
“…This is in line with the findings of Danish DREAM studies where the associations of physical and psychosocial work factors, measured at one time point, were studied with sickness absence (15). The difference in the strength of the association between the physical and psychosocial working conditions may be due to the fact that physical working conditions are more directly associated with sickness absence as the assessment of work ability includes taking the requirements of work tasks into account.…”
Section: Discussionsupporting
confidence: 85%
“…This is in line with the findings of Danish DREAM studies where the associations of physical and psychosocial work factors, measured at one time point, were studied with sickness absence (15). The difference in the strength of the association between the physical and psychosocial working conditions may be due to the fact that physical working conditions are more directly associated with sickness absence as the assessment of work ability includes taking the requirements of work tasks into account.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have, for example, shown that work environmental factors, mainly physical but also psychosocial factors (Burr et al, 2011;Christensen et al, 2005;Labriola et al, 2006;Lund et al, 2006;Nielsen et al, 2006;Voss et al, 2004), lifestyle Robroek et al, 2011), and pain (Saastamoinen et al, 2009) are associated with SA. Further, some recent twin studies of the associations between socio-demography, health-related factors, pain, and DP showed that the associations seem to be independent from familial effects or influenced by those to a minor degree (Pietikäinen et al, 2011;Ropponen et al, 2011aRopponen et al, , 2011bSamuelsson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The DWECS is an open cohort study initiated in 1990 with a random sample of people, aged 18-59 years, in the Danish population. The cohort has thereafter been supplemented with young people and immigrants so as to obtain a representative cross-sectional study of ≥5000 employees every fifth year (22). The reported response rates were 80%, 75%, 60%, 62%, 66%, and 48% for DWECS 1995 (16) …”
Section: Data Materialsmentioning
confidence: 99%